Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

We consider the following function.

$$u(x) = \int_{0}^{x} \frac{dt}{\sqrt{1 - t^4}}$$

$u(x)$ is defined on $[-1, 1]$. Since $u'(x) = \frac{1}{\sqrt{1 - x^4}} > 0$ on $(-1, 1)$, $u(x)$ is strctly increasing on $[-1, 1]$. Hence there exists the inverse function of $u(x)$. We denote the inverse function of $u(x)$ by $s(u)$. We call $s(u)$ lemniscate sine(see this question).

By the binomial series expansion,

$\frac{1}{\sqrt{1 - x^4}} = \sum_{k=0}^{\infty} {k-\frac{1}{2} \choose k}x^{4k}$

This series converges uniformly on $|x| \le \rho$, where $\rho$ is any real number such that $0 < \rho < 1$.

Hence when $|x| \le \rho$,

$u(x) = \int_{0}^{x} \frac{dx}{\sqrt{1 - x^4}} = \sum_{k=0}^{\infty} \int_{0}^{x} {k-\frac{1}{2} \choose k}x^{4k} dx = \sum_{k=0}^{\infty} \frac{1}{4k+1}{k-\frac{1}{2} \choose k}x^{4k+1}$

Then the power series expansion of $s(u)$ can be calculated as a formal power series.

$s(u) = u -\frac{1}{10}u^5 + \frac{1}{120}u^9 + \frac{11}{15600}u^{13}+ \frac{211}{353600}u^{17}+\cdots$

My question How do we prove that the power series expansion of $s(u)$ is of the following form?

$s(u) = \sum_{k=0}^{\infty} b_{4k+1}u^{4k+1}$

share|cite|improve this question

An analytic function $f(z)$ has Maclaurin series of the form $\sum_k b_{4k+1} z^{4k+1}$ iff $f(iz) = i f(z)$ for all $z$ in a neighbourhood of $0$. If $g(z) = 1/(1 - z^4)^{1/4}$ we have $g(iz) = g(z)$. Now $u(z)$ is an antiderivative of $g(z)$ in a neighbourhood of $z=0$ with $u(0) = 0$; since $v(z) = u(iz)/i$ also has $v(0) = 0$ and $v'(z) = u'(iz) = g(iz) = g(z)$, we must have $v(z) = u(z)$ in a neighbourhood of $0$, i.e. $u(iz) = i u(z)$ there. And then $s(z)$ is the unique inverse function of $u(z)$ on a neighbourhood of $0$: $s(iz) = w$ where $u(w) = iz$, but since $u(is(z)) = u(s(iz)) = iz$ we have $w = i s(z)$, i.e. $s(iz) = i s(z)$ in some neighbourhood of $0$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.